STUDI PEMANFAATAN POTENSI AIR WADUK SERMO UNTUK PELAYANAN AIR BAKU - , Arian Pratama ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As the era becoming more advanced and population grows more rapidly, the demand for goods and services derived from water resource will increase. The excessive usage of water resources can cause problems such as lack of water. The purpose of this study was to find out how to utilize the potential of Sermo Reservoir as a raw water resource with optimum result, and to find out the availability of water in the Sermo Reservoir. This research used the water scale method to find its historical inflow, the data was then developed using the Thomas â Fiering method, and the calculation on the needs of the raw water is calculated based on the regulation of Ditjen Cipta Karya. This research was conducted using the SOR (standard operating rule) method to simulate the reservoirâs reliability in fulfilling the needs of water in the region it serves. The results show that water available in Sermo Reservoir is inadequate to 100% supply the needs of raw water. Sermo Reservoir optimal capability to stock up the needs of raw water in the Kokap, Pengasih, Temon, Wates, Panjatan, and Sentolo region is at the level of 47 % of the entire area it serves with a success rate of 100 %